Climate change and its impacts in Southern Africa: A synthesis of existing evidence in support of the World Food Programme’s 2021 Climate Change Position Paper - Ramírez Villegas, Julián Armando; Ghosh, Aniruddha; Craparo, Sandro; Thornton, Philip K.; Manvatkar, Rupak; Bogart, Brian; Läderach, Peter R.D. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Approximately 30% of the whole SADC region is exposed to a variety of climate hazards and their combinations. Decreased suitable land for cropping and reduced crop and livestock production would exacerbate water scarcity and insecurity, and decrease national self-sufficiency ratios, and impact food availability locally, with devastating effects on food insecurity in the region. Water, energy and food are inextricably linked across multiple scales in SADC and are heavily interdependent. Therefore, actions to address climate change need to be regionwide. Furthermore, addressing existing and emerging water-energy-food issues requires understanding and shaping ongoing food systems transformations in the region.